Identification of Sialyl-Lewis(x)-Interacting Protein on Human Spermatozoa - Wang, Ying; Zhao, Weie; Mei, Si; Chen, Panyu; Leung, Tsz-Ying; Lee, Cheuk-Lun; Yeung, William S. B.; Ou, Jian-Ping; Liang, Xiaoyan; Chiu, Philip C. N. (Frontiers in Cell and Developmental Biology, 2021)
Capacitated spermatozoa initiate fertilization by binding to the zona pellucida (ZP). Defective spermatozoa-ZP binding causes infertility. The sialyl-Lewis(x) (SLeX) sequence is the most abundant terminal sequence on the glycans of human ZP glycoproteins involving in spermatozoa-ZP binding. This study aimed to identify and characterize the SLeX-binding proteins on human spermatozoa. By using affinity chromatography followed by mass spectrometric analysis, chromosome 1 open reading frame 56 (C1orf56) was identified to be a SLeX-binding protein of capacitated spermatozoa. The acrosomal region of spermatozoa possessed C1orf56 immunoreactive signals with intensities that increased after capacitation indicating translocation of C1orf56 to the cell surface during capacitation. Treatment with antibody against C1orf56 inhibited spermatozoa-ZP binding and ZP-induced acrosome reaction. Purified C1orf56 from capacitated spermatozoa bound to human ZP. A pilot clinical study was conducted and found no association between the percentage of capacitated spermatozoa with C1orf56 expression and in vitro fertilization (IVF) rate in assisted reproduction treatment. However, the percentage of C1orf56 positive spermatozoa in the acrosome-reacted population was significantly (P<0.05) lower in cycles with a fertilization rate <60% when compared to those with a higher fertilization rate, suggesting that C1orf56 may have functions after ZP-binding and acrosome reaction. A larger clinical trial is needed to determine the possible use of sperm C1orf56 content for the prediction of fertilization potential of sperm samples.